Analisis Kesetaraan Gender dalam Implementasi Program Pembangunan dan Pemberdayaan Masyarakat (PROBEBAYA) di Kantor Walikota Samarinda - Juwita Hartati; Asnar Asnar; Endang Herliah; Jamil Jamil; Marwiah Marwiah; Novita Novita (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The aim of this research is to find out how gender equality is implemented through the community development and empowerment program (probebaya) in the Samarinda Mayor's office, then what obstacles exist, as well as the efforts made in implementing probebaya to realize gender equality in Samarinda City. Type of descriptive qualitative research. The research was conducted at the Mayor of Samarinda's office in March 2024 - May 2024. The subject of this research was the Head of the BAPPERIDA Sub-Government Team, Samarinda Community Self-Help Activator JabFung DP2PA, BAPPERIDA Community Equality and Welfare JabFung using observation, interview and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation, and data conclusion. The research results show that the analysis of gender equality in the implementation of development and community empowerment programs (probebaya) at the Samarinda Mayor's Office has been carried out evenly, starting from the roles of men, women and people with disabilities. This Probebaya program is also purely from, by and for the community. This is because the impact can be felt directly by the community itself, starting from the infrastructure sector, the economic sector, the socio-cultural sector, the health sector, the education sector and the youth sector, all of which are implemented at the RT level on a small scale.